Qualidade de Contexto em uma Infraestrutura para Navegação Indoor. - SOUSA, Tércio Santana Silva (2019)
The ubiquitous computing is a research area of the computer science that defines the environments equipped with devices capable of making the interaction between humans and computers invisible and omnipresent. Context awareness describes the applications able to identify characteristics of the environment in which they are inserted and to adapt their behavior to provide customized services according to this information. The combination of the ubiquitous computing with the context awareness has allowed the development of new applications and research areas such as indoor location, which has gained attention in recent years with the purpose to solve the indoor location problems due to GPS provides accuracy acceptable only in outdoor environments. This study was conducted in the context of the INavigS architecture, which provides services for indoor navigation using mobile devices, such as smartphones. Despite offering the proposed services, problems such as low localization precision, lack of context data that define user orientation and high response time for display of navigational instructions were identified. The present work aims to propose solutions in the context of context quality aiming to improve its experience of use and provision of more efficient services.